Using social media to measure the contribution of red list species to the nature - based tourism potential of African protected areas :Powerpoint - Cottam, A.J. (University of Twente, 2020)
This lecture presents: Cultural es: nature-based tourism; Online sources; Online image counts; Flickr search results; Attractive species in protected areas; Validity of the new tourism-potential indicator; Attractive species, global; Conservation and attractive species.